Angiotensin Type 2 Receptor Gene Polymorphisms and Susceptibility to Preeclampsia - MS Soltani-Zangbar; B Pahlavani; J Zolghadri; B Gharesi-Fard (JRI, 2018)
Background: The purpose of the study was to determine the relationship between angiotensin II type 1 receptor at position+1166 (AT1R+1166A/C; rs5186) and angiotensin II type 2 receptor at position+1675 (AT2R+1675A/G; rs5194) gene polymorphisms with preeclampsia in an Iranian women population. Methods: 430 women were recruited in this study including 212 preeclamptics and 218 healthy women. PCR-RFLP method was used for genotyping the polymorphisms. Chi square and Fisher exact test were used for comparing case and control groups. The p<0.05 was considered statistically significant. Results: The frequency of genotypes of the AT1R gene and AT2R gene was similar in preeclampsia and normal pregnancy. There were no significant differences in genotype and also allele frequencies between preeclamptics and healthy women regarding the two studied polymorphisms. AT1R/AT2R genotypes combination study indicated that there was a statistically significant difference between preeclamptics and healthy women. AC/AG combination was significantly decreased, while CC/AA combination showed significant increase in patients compared with the healthy women (p<0.01). Conclusion: The present study showed that the genetic polymorphisms within AT1R and AT2R genes may be associated with susceptibility to preeclampsia in Iranian women.